Conceptual Evolution of City Branding: A Systematic Review and the Progress of the Terms Social Media and Smart City in Literature - Albayrak Fakioglu, Pelin; Oguztimur, Senay (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2025)
The aim of this study is to examine the evolution of the city branding concept and to explore the development of smart city and social media terms in city branding literature, from January 1st, 2003, to August 1st, 2023. Conducting a systematic review of 325 peer-reviewed English articles from the Emerald, Proquest, and Web of Science (WoS) databases that feature city branding or city marketing in their abstracts, keywords, or titles, the study assesses the transition from simpler branding strategies to complex and integrated approaches over the two-decade period. The research reveals an uptick in concept-related research since 2010, particularly highlighting the growing significance of smart city and social media concepts within the city branding literature. Furthermore, it identifies an increased focus on city branding efforts in Chinese cities over the last decade. By providing a comprehensive review of the developments and changes in city branding, alongside the evolving roles of smart city and social media concepts, this article is expected to contribute valuable insights to the existing body of literature.
Keywords: City Branding; City Marketing; Social Media; Social Media Marketing; Smart City; Smart City Branding; STAKEHOLDERS; CULTURE; Business & Economics